IMPLEMENTASI E-PKL PADA DINAS PERHUBUNGAN JEPARA - Aulya Shabrina Aisyane; Joko Minardi; Heru Saputro (Journal of Information System and Computer, 2023)
Field Work Practice is a learning activity that aims to introduce and expand students' skills in the real world of work. One of the PKL places that opens opportunities for students to carry out tasks is the Jepara Transportation Office. The Transportation Agency is a regional government organizing body in the field of transportation. But unfortunately, until now the Jepara Transportation Office does not have a system that can facilitate students and management staff to manage these PKL activities. This results in many documents that range lost and not well documented. The PKL information system with criteria assessment using a Likert scale is a solution in the PKL management process for the better. This application is web-based so that all data is managed and stored properly. This system has gone through the black box testing stage with the results of all features, flows, and programs that are normal and in accordance with what was planned at the beginning. In addition, the percentage of feasibility from the results of testing through a questionnaire to 12 respondents (users) of the Jepara Transportation Office E-PKL system received a score of 90.5% which means it is very feasible to use.